2016
DOI: 10.1177/0194599816644915
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Middle versus Inferior Total Turbinectomy on Nasal Aerodynamics

Abstract: Objectives This computational study aims to: (1) Use virtual surgery to theoretically investigate the maximum possible change in nasal aerodynamics after turbinate surgery; (2) Quantify the relative contributions of the middle and inferior turbinates to nasal resistance and air conditioning; (3) Quantify to what extent total turbinectomy impairs the nasal air conditioning capacity. Study Design Virtual surgery and computational fluid dynamics (CFD). Setting Academic tertiary medical center. Subjects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 43 publications
2
62
0
Order By: Relevance
“…Subjective nasal patency; nasal airflow sensation; nasal mucosal temperature; mucosal cooling; NOSE score; visual analog scale; nasal airway obstruction Recent computational studies demonstrated that it is possible to quantify inspiratory mucosal heat loss utilizing computational fluid dynamics (CFD) simulations in 3-dimensional patient-specific models of the nasal anatomy built from radiologic imaging. [15][16][17][18] These computational studies confirmed that subjective nasal patency correlates better with mucosal heat loss than with nasal resistance to airflow. 16,18 The CFD technique, however, has some disadvantages, including the high cost of medical imaging, radiation exposure when based Bailey et al…”
Section: Introductionsupporting
confidence: 59%
“…Subjective nasal patency; nasal airflow sensation; nasal mucosal temperature; mucosal cooling; NOSE score; visual analog scale; nasal airway obstruction Recent computational studies demonstrated that it is possible to quantify inspiratory mucosal heat loss utilizing computational fluid dynamics (CFD) simulations in 3-dimensional patient-specific models of the nasal anatomy built from radiologic imaging. [15][16][17][18] These computational studies confirmed that subjective nasal patency correlates better with mucosal heat loss than with nasal resistance to airflow. 16,18 The CFD technique, however, has some disadvantages, including the high cost of medical imaging, radiation exposure when based Bailey et al…”
Section: Introductionsupporting
confidence: 59%
“…Researchers have explored a myriad of topics, such as characterizing nasal airflow in healthy subjects (Zhao and Jiang, 2014), quantifying nasal filtration of airborne particles (Frank-Ito et al, 2015; Garcia et al, 2015b; Schroeter et al, 2011; Schroeter et al, 2015), heating and humidification of inspired air (Dayal et al, 2016; Goodarzi-Ardakani et al, 2016), the relationship between nasal function and nasal anatomy (Garcia et al, 2016; Patki and Frank-Ito, 2016), and airflow in the paranasal sinuses (Zhu et al, 2012; Zhu et al, 2014). In particular, there is much interest in identifying flow variables that correlate with symptoms of nasal airway obstruction (Garcia et al, 2016; Garcia et al, 2010; Hariri et al, 2015; Kim et al, 2014; Na et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This manuscript is part of a larger study investigating the correlation between subjective and objective measures of nasal airflow (Dayal et al, 2016; Frank-Ito et al, 2014; Garcia et al, 2016; Hariri et al, 2015; Kimbell et al, 2013; Patel et al, 2015; Rhee et al, 2014; Sullivan et al, 2014). The cohort consisted of 27 patients all undergoing surgery to treat chronic nasal airway obstruction (septoplasty, turbinectomy, and/or functional rhinoplasty).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in the CFR models studied, only an anterior septal strut and inferior turbinates remained after surgery. Given that extensive intranasal surgery has been correlated with ineffective air conditioning, it is reasonable to assume that CFR patients would report symptoms of congestion, dryness, and crusting. However, the majority deny significant nasal complaints in the long‐term postoperative period .…”
Section: Discussionmentioning
confidence: 99%
“…Nasal humidification efficiency, previously described by Dayal et al, was defined as: normalΣ humidification 0.28em=100×false(normalC postseptum normalC nostril false)/normalC mucosa normalC nostril )where C nostril , C postseptum , and C mucosa are the water concentrations in air at the nostril, posterior septum, and nasal mucosa, respectively. This represents the overall transport of water from nasal mucosa during inspiration.…”
Section: Methodsmentioning
confidence: 99%